Invention and innovation : a brief history of hype and failure - Smil, Vaclav (The MIT Press, 2023)
"Smil presents the long history and modern infatuation with invention and innovation. Meticulous as always, these vast realms of human ingenuity are organized into sensible categories: inventions that went from welcome to undesirable, inventions that dominate and missed the mark, inventions we still dream about, and lastly, the exaggerations, myths, and wise expectations for innovations we need most"--